Incentive spirometry for prevention of postoperative pulmonary complications in upper abdominal surgery - Nascimento Junior, Paulo do [UNESP]; Módolo, Norma Sueli Pinheiro [UNESP]; Andrade, Silvia [UNESP]; Guimaraes, Michele M. F.; Braz, Leandro Gobbo [UNESP]; El Dib, Regina [UNESP] (Wiley-Blackwell, 2014)
BackgroundThis is an update of a Cochrane Review first published in The Cochrane Library 2008, Issue 3.Upper abdominal surgical procedures are associated with a high risk of postoperative pulmonary complications. The risk and severity of postoperative pulmonary complications can be reduced by the judicious use of therapeutic manoeuvres that increase lung volume. Our objective was to assess the effect of incentive spirometry compared to no therapy or physiotherapy, including coughing and deep breathing, on all-cause postoperative pulmonary complications andmortality in adult patients admitted to hospital for upper abdominal surgery.ObjectivesOur primary objective was to assess the effect of incentive spirometry (IS), compared to no such therapy or other therapy, on postoperative pulmonary complications and mortality in adults undergoing upper abdominal surgery.Our secondary objectives were to evaluate the effects of IS, compared to no therapy or other therapy, on other postoperative complications, adverse events, and spirometric parameters.Search methodsWe searched the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library 2013, Issue 8), MEDLINE, EMBASE, and LILACS (from inception to August 2013). There were no language restrictions. The date of the most recent search was 12 August 2013. The original search was performed in June 2006.Selection criteriaWe included randomized controlled trials (RCTs) of IS in adult patients admitted for any type of upper abdominal surgery, including patients undergoing laparoscopic procedures.Data collection and analysisTwo authors independently assessed trial quality and extracted data.Main resultsWe included 12 studies with a total of 1834 participants in this updated review. The methodological quality of the included studies was difficult to assess as it was poorly reported, so the predominant classification of bias was 'unclear'; the studies did not report on compliance with the prescribed therapy. We were able to include data from only 1160 patients in the meta-analysis. Four trials (152 patients) compared the effects of IS with no respiratory treatment. We found no statistically significant difference between the participants receiving IS and those who had no respiratory treatment for clinical complications (relative risk (RR) 0.59, 95% confidence interval (CI) 0.30 to 1.18). Two trials (194 patients) IS compared incentive spirometry with deep breathing exercises (DBE). We found no statistically significant differences between the participants receiving IS and those receiving DBE in the meta-analysis for respiratory failure (RR 0.67, 95% CI 0.04 to 10.50). Two trials (946 patients) compared IS with other chest physiotherapy. We found no statistically significant differences between the participants receiving IS compared to those receiving physiotherapy in the risk of developing a pulmonary condition or the type of complication. There was no evidence that IS is effective in the prevention of pulmonary complications.Authors' conclusionsThere is low quality evidence regarding the lack of effectiveness of incentive spirometry for prevention of postoperative pulmonary complications in patients after upper abdominal surgery. This review underlines the urgent need to conduct well-designed trials in this field. There is a case for large RCTs with high methodological rigour in order to define any benefit from the use of incentive spirometry regarding mortality.
Keywords: Abdomen [surgery]; Bronchial Diseases [prevention & control]; Lung Diseases [prevention & control]; Pneumonia [prevention & control]; Postoperative Complications [prevention & control]; Pulmonary Atelectasis [prevention & control]; Randomized Controlled Trials as Topic; Respiratory Insufficiency [prevention & control]; Respiratory Therapy [methods]; Spirometry [methods]; Tracheal Diseases [prevention & control]; Adult; Humans